Surgery of Epilepsy - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1992)
The surgical outcome in 34 patients between 2 and 15 years of age who were operated on for medically intractable seizures is reported from the Neurosurgical Clinic, University Clinical Center, Visegradska 26, Belgrade, Yugoslavia.